THE UTILIZATION OF ISLAMIC-BASED TEXTS FOR CHARACTER INNOVATION: EFL STUDENTS' PERCEPTION - Roslaini, Roslaini; Ithriyah, Siti; Purnama Sari, Ika; Harun, Makmur (Jurnal As-Salam, 2023)
Law Number 20 of 2003 emphasizes character education in the Indonesian National Education System, which functions to develop competence and build the character of students who are devout and have faith in God Almighty. The material should be combined with a religious approach to fulfill these expectations. This research explores EFL students' perceptions of utilizing Islamic-based texts for teaching reading. The respondent was a Muhammadiyah University student, Prof. Dr. HAMKA. 36 students participated in responding to questionnaires and interviews. The results show that most EFL students benefit from using Islamic-based texts on their knowledge, attitudes, and skills. It has implications for using Islamic-based texts that can shape student character and behavior. With this method, in the end, students can read critically and understand the text, which also greatly influences their character and behavior.